Dealing with the legacy of dictatorship : Indonesia and Philippines - Yoes, C. Kenawas (2012)
Indonesia and the Philippines recently observed anniversaries of two crucial events, which involved massive human rights violations and led to the establishment of authoritarian regimes in both countries. However, justice for the victims of mass atrocities remains elusive.